(untitled) (Communication & Society, 1998)
This article carries out a weighed des cription of the methods and approaches of research on the effects of election campaigns, as well as their accommodation to the proposal of the "cultural perspective". After analyzing the elements which mitigate those effects and following the traditional schema that distinguishes cognitions, attitudes and behaviors, the author analyzes the effects of the images of the candidates, electoral debates and political spots on television. The revision of some theories that inspire research on effects -such as the "theory of selective perception", the "theory of priming", and the "theory on agenda setting"- concludes by stating the need for revising the traditional schema for measuring these effects.